Evaluation of Myocardial Deformation in Patients with Sickle Cell Disease and Preserved Ejection Fraction Using Three-Dimensional Speckle Tracking Echocardiography - Ahmad, Homaa (2012)
Sickle cell disease (SCD) is a hemoglobinopathy that affects one in 500 African Americans. Although it is well established that patients with SCD have left ventricular (LV) diastolic dysfunction, it is not clear whether they have subtle LV systolic dysfunction despite preserved ejection fraction (EF). We used three-dimensional speckle tracking echocardiography (3D STE) to assess changes in both systolic and diastolic LV function in SCD. METHODS: Transthoracic real-time 3D images were obtained (Philips iE33) in 56 subjects, including 28 stable outpatients with SCD (age 33±7 years) and 28 normal controls (age 35±9 years). 3D-STE was performed using prototype software (4DLV Analysis, TomTec) to obtain LV volume and deformation time-curves, from which indices of systolic and diastolic LV function were calculated. RESULTS: In SCD patients, 3D-STE derived LV filling parameters were significantly different from normal controls, reflecting an increase in both rapid and atrial filling volumes and prolonged active relaxation, depicted by a decrease in filling volume fractions at fixed times and an increase in rapid filling duration. Global LV systolic function was not only preserved but increased compared to controls, as reflected by significantly increased global longitudinal strain. Importantly, twist angle and torsion as well as radial and circumferential components of 3D strain were similar in both groups. CONCLUSIONS: 3D-STE was able to confirm diastolic dysfunction, as expected in some patients with SCD. However, 3D-STE strain analysis did not reveal any changes in LV systolic function. These findings provide novel insight into the pathophysiology of the cardiovascular complications of SCD.